(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This paper examined various factors responsible for poor students’ academic performance in schools in Nigeria. Depending on secondary data obtained from recognized online and print resources. The paper concluded that factors responsible for poor students’ academic performance in schools in Nigeria includes; presence of unqualified teacher in the schools, shortage of professional teachers, poor motivation of teachers, inadequate infrastructure facilities, poor supervision, leadership styles of school administrators, student’s health status, parents and guardians socio-economic status, poor usage of instructional resources, large class size and poor classroom management practices by teachers. Based on the factors identified, the paper hereby recommended the following: Adequate funding of educational institutions. This will enable school administrator procure all human and materials resources require to ensure quality educational standard and improve students’ performance. Employment of more professional teaching and special program should be organized for the unprofessional teachers to upgrade their certificates and training. Government should motivate teachers by increasing their salaries, allowances and provide conducive working environment. He should also provide adequate infrastructure facilities, instructional resources, ensure effective training program and prompt payment of their salaries. School administrators should be trained on the use of effective leadership and effective motivational strategies. Teachers should be trained on modern classroom management practices. This will help to improve their job performance and students’ academic performance.